Immediate and short-term effects of continuous theta burst transcranial magnetic stimulation over contralesional premotor area on post-stroke spasticity in patients with severe hemiplegia: Study protocol for a randomized controlled trial - Wei, Xiupan; Xia, Nan; Li, Yang-An; Gu, Minghui; Zhang, Tongming; Gao, Wei; Liu, Yali (Frontiers in Neurology, 2022)
Background: Post-stroke spasticity is an important complication that greatly affects survivors' functional prognosis and daily activities. Increasing evidence points to aberrant contralesional neuromodulation compensation after brain injury as a possible culprit for increased spasticity in patients with severe stroke. Hyperactivity of the contralesional premotor area (cPMA) was supposed to be highly correlated with this progression. This study aims to demonstrate the immediate and short-term efficacy of continuous theta-burst stimulation (cTBS) targeting cPMA on upper limb spasticity in severe subacute stroke patients. Methods: This trial is a single-center, prospective, three-group randomized controlled trial. 45 eligible patients will be recruited and randomized into three groups: the sham-TBS group (sham TBS targeting contralesional PMA), the TBS-cM1 group (TBS targeting contralesional M1), and the TBS-cPMA group (TBS targeting contralesional PMA). All subjects will undergo comprehensive rehabilitation and the corresponding TBS interventions once a day, five times a week for four weeks. Clinical scales, neurophysiological examinations, and neuroimaging will be used as evaluation tools. As the primary outcome, clinical performance on muscle spasticity and upper-limb motor function will be evaluated with the modified Ashworth scale and the Fugl-Meyer Assessment respectively. These scores will be collected at baseline, after 4 weeks of treatment, and at follow-up. The secondary outcomes were neurophysiological examinations and Neuroimaging. Motor evoked potentials, startle reflex, and H reflexes will be used to assess the excitability of the subject's motor cortex, reticulospinal pathway, and spinal motor neurons, respectively. Results will be recorded before and after the first TBS treatment, at post-intervention (at 4 weeks), and at follow-up (at 8 weeks). Neuroimaging tests with diffusion tensor imaging for all participants will be evaluated at baseline and after the 4-week treatment. Discussion: Based on the latest research progress on post-stroke spasticity, we innovatively propose a new neuromodulation target for improving post-stroke spasticity via cTBS. We expected that cTBS targeting cPMA would have significant immediate and short-term effects on spasticity and related neural pathways. The effect of TBS-cPMA may be better than that of TBS via cM1. The results will provide robust support for the application of cTBS neuromodulation in post-stroke spasticity after a severe stroke.